2017
DOI: 10.1002/lt.24745
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous vascular endothelial growth factor delivery prior to endothelial precursor cell transplantation in orthotopic liver transplantation–induced hepatic ischemia/reperfusion injury

Abstract: Vascular endothelial growth factor (VEGF) promotes angiogenesis in vivo. We hypothesized that exogenous delivery of VEGF prior to bone marrow-derived endothelial precursor cell (EPC) transplantation may improve orthotopic liver transplantation (OLT)-induced hepatic ischemia/reperfusion injury (HIRI). OLT between Sprague Dawley donor rats and inbred LEW Wistar recipient rats was performed in 6 experimental groups to comparatively assess the effects of the VEGF gene: an untreated normal control group, a surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Many studies have demonstrated that the mechanism triggered by transplanted cells significantly contributes to liver IRI [31, 32]. Various proteins secreted by DCs play important roles in the improvement of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the mechanism triggered by transplanted cells significantly contributes to liver IRI [31, 32]. Various proteins secreted by DCs play important roles in the improvement of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…DockThor online tool was used to carry out molecular docking of these target gene receptors and their corresponding small molecule conjugated ligands, and the results are shown in Table 2 . Cao et al (2017) recently reported that before bone marrow–derived endothelial progenitor cell transplantation, exogenous liposome delivery of VEGF gene may be an effective strategy to reduce orthotopic liver transplantation–induced HIRI. Jiao et al (2021) reported that VEGF and IL-6 play an important role in the study of the potential of mesenchymal stem cell secretome to promote liver regeneration after hepatic ischemia/reperfusion combined with partial resection.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of taking-up of composite grafts, inadequate tissue perfusion and ischemia-reperfusion injury are critical factors determining graft survival. The protective effect of VEGF on ischemia-reperfusion injury has been well established in transplantation surgery, such as kidney, lung and liver procedures [11][12][13], and those reports stated that VEGF affected endothelial cell survival, regulating their proliferation, regeneration, and apoptosis. Therefore, we expect that PDRN has the potential to improve the survival of composite grafts, enhancing neovascularization and protecting against ischemia-reperfusion injury by mediating an increase in VEGF.…”
Section: Discussionmentioning
confidence: 99%